PERKEMBANGAN PENDIDIKAN ISLAM DI ERA MILENIAL - Astuti, Mardiah; Herlina, Herlina; Ibrahim, Ibrahim; Nupus, Fiona Hayatun; Meilinda, Nina; Miranti, Miranti (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract: Islamic education in the current millennial era has experienced significant developments throughout its history, in this millennial era as well. In today's digital and information technology era, the development of Islamic education faces new challenges and an opportunity. It presents how Islamic education adapts to social trends and changes in the current millennial era. The research method used is descriptive qualitative method, with a descriptive approach. The informants of this study were 9 students of the Raden Fatah State University of Palembang, Indonesia. Data was collected through observation, literature study and interviews. Data analysis used descriptive qualitative analysis, so that in-depth conclusions were obtained from the problems studied. The results of this study are first, the form of challenges that occur in the development of Islamic education in the millennial youth era which often occur in the present are: (1) the influence of social media (2) the influence of outside culture (3) technological advances (4) moral decadence ( 5) minimal understanding of religion (6) moral challenges. Researchers found challenges that could affect the development of Islamic education in the current millennial era. Second, important factors that can influence Islamic education in the current millennial era are: (1) having a solid Islamic foundation (2) having strong moral values (3) overcoming the challenges of the times (4) forming an identity (5) build an understanding of Islam (6) develop morals. these factors strengthen to fight challenges in the development of Islamic education in the millennial era.Keywords: Islamic Education, Millennial Era